THE ROLE OF PHARMACY IN MEDICATION MANAGEMENT FOR MENTAL DISEASES WITH A HOLISTIC APPROACH - Meilinda, Vivi; Zuhriyah, Nabilaa Faizatuz; Alifah, Nur (Jurnal Kesehatan, 2025)
This study aims to explore the role of pharmacy in drug management for mental illness with a holistic approach. Although pharmacological treatment plays an important role in managing mental disorders, this research emphasizes the importance of a more holistic approach involving pharmaceuticals, psychotherapy, and lifestyle changes. The research method used was qualitative with a case study design involving 10 patients, 5 pharmacists and 5 psychiatrists in two hospitals in Jakarta. Data was collected through in-depth interviews, questionnaires and direct observation. The research results show that although pharmacists are involved in drug management, their involvement in a holistic approach is still limited to pharmacotherapy aspects. Collaboration between pharmacists and psychiatrists was found to be important to improve patient compliance with treatment, but the implementation of a holistic approach that includes psychosocial aspects is still lacking. These findings imply that hospitals need to develop training programs for pharmacists and increase interprofessional collaboration to create more comprehensive mental illness treatment. This research provides important insights into how pharmacy can play a greater role in supporting a holistic approach to the treatment of mental illness.